Avaliação de recursos e estratégias didáticas sobre botânica na perspectiva de professores de biologia da educação básica - Nathália dos Santos Silva (2022)
Teachers may observe some students with low interest in understanding what is proposed in the classes. This low motivation can result in less efficient learning. This is a problem, since learning is fundamental for students’ autonomy and leading hole in their story. In traditional teaching, the teacher acts as the agent, the holder of knowledge and the active entity in the classroom, while the students are just passive receivers. However, it is expected that the school must form critical and autonomous young people by methods focused on developing the students’ thinking and linked to different practices and techniques of teaching. To achieve these objectives and reducing the passivity of the students, didactic tools and strategies for teaching botany were proposed here to aid teachers to motivate students and contribute to their capacity to lead with other activities related with this topic, such as exams. A didactic sequence for botany classes, composed of different teaching and evaluation strategies, was elaborated. Its total or partial applicability was evaluated by High School teachers. The sequence was composed of varied activities, which, together or separately, may help teachers to improve their students' ability to learn, investigate, practice, share, and produce knowledge. It was proposed the application of a diagnostic and evaluative questionnaire, reading a basic text about plants in everyday life, investigative activities, dialogued lectures, assembly of an illustrated glossary, creation of a didactic game, and the creation of an interactive video. In general, the teachers evaluated the sequence positively, and it was also noticeable that personal characteristics and experiences influenced each teacher when choosing the activities to adopt in their classes.